2021
DOI: 10.1002/jpln.202000527
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific root interactions increase maize yields in intercropping with different companion crops

Abstract: Background Intercropping is assumed to increase food production while reducing fertilizer needs and environmental impacts of crop production. Aims We aimed to (1) investigate the effects of intercropping on yields and nutrient uptake of maize, and (2) determine the relative contributions of above‐ and belowground interspecific interactions (RCabove/below) to these effects. Methods We conducted a 2‐year, small‐scale field experiment with maize grown either in monocropping or intercropped with faba bean, soy, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Thus, maize plants could potentially benefit from intercropping with one of the other plant species if the different plant species have a joint rhizosphere in which complementary and facilitative interactions can occur. Such positive intercropping effects on maize have been proposed earlier in various studies on intercropping (Homulle et al 2022;Li et al 2020a;Schwerdtner and Spohn 2021;Tang et al 2021). Moreover, plant species that effectively mobilize P from different soil P pools (such as soy and mustard) could potentially be used in crop rotations and/or as cover crops with likely positive effects on the P uptake of subsequent crops (Hallama et al 2019).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, maize plants could potentially benefit from intercropping with one of the other plant species if the different plant species have a joint rhizosphere in which complementary and facilitative interactions can occur. Such positive intercropping effects on maize have been proposed earlier in various studies on intercropping (Homulle et al 2022;Li et al 2020a;Schwerdtner and Spohn 2021;Tang et al 2021). Moreover, plant species that effectively mobilize P from different soil P pools (such as soy and mustard) could potentially be used in crop rotations and/or as cover crops with likely positive effects on the P uptake of subsequent crops (Hallama et al 2019).…”
Section: Discussionmentioning
confidence: 78%
“…In the field, soy and lupin seeds had been inoculated with commercial Bradyrhizobium sp. inoculants, which are assumed to be also part of the microbial community introduced here (for details, see Schwerdtner and Spohn 2021). The soil was sieved (< 2 mm), mixed with tap water (1:2), and shaken on an overhead shaker for 1 h before being filtered through cellulose filters (Rotilabo®,type 113P,Carl Roth GmbH & Co. KG,Karlsruhe,Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The acidification of the rhizosphere by exudates from the Cp likely benefited the intercropped Dw by increasing P availability through the dissolution of P minerals [ 26 ]. In addition, Schwerdtner et al [ 20 ] reported that Cp species secrete higher levels of phosphatase in P-deficient soil conditions through their root systems. These results support the idea that cluster-root formation plays a significant role in acquiring P from alluvial soils under semi-arid climates.…”
Section: Resultsmentioning
confidence: 99%
“…An inoculum was applied to the mineral substrate at the beginning of the experiment to introduce a soil microbial community. For this purpose, fresh soil (with a loamy sandy texture) was sampled from an agricultural field (for details see Schwerdtner & Spohn, 2021). The soil was sieved (<2 mm), mixed with tap water (1:2) and shaken on an overhead shaker for 1 h before being filtered through cellulose filters (Rotilabo®, type 113P; Carl Roth GmbH & Co. KG).…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, fresh soil (with a loamy sandy texture) was sampled from an agricultural field (for details see Schwerdtner & Spohn, 2021).…”
Section: Methodsmentioning
confidence: 99%